2003
DOI: 10.1101/lm.62903
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Induced Amnesia in Rats: Working Memory-Specific Impairment, Corticosterone-Memory Correlation, and Fear Versus Arousal Effects on Memory

Abstract: We have shown previously that psychological stress (predator exposure) impairs spatial memory in rats. We have extended that finding here to show that predator stress selectively impaired recently acquired (hippocampaldependent) spatial working memory without affecting long-term (hippocampal-independent) spatial reference memory. We also investigated why predator exposure impairs memory. Was spatial memory impaired because of the fear-provoking aspects of predator exposure or only because the cat was a novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 112 publications
(168 reference statements)
11
107
2
4
Order By: Relevance
“…Acute exposure to predator odor impairs working memory, a result consistent with alterations in mesoprefontal dopamine activity (Morrow et al 2000). Additional work has shown that acute predator stress impairs long-term hippocampal-dependent spatial memory and this impairment is associated with altered gene expression in the hippocampus and the prefrontal cortex (Diamond et al 1999;Sandi et al 2005;Woodson et al 2003). The ability of predator stress to facilitate recall of and responsiveness to a previously conditioned context is another novel finding of this study.…”
Section: Conditioned Locomotor Arousalsupporting
confidence: 63%
“…Acute exposure to predator odor impairs working memory, a result consistent with alterations in mesoprefontal dopamine activity (Morrow et al 2000). Additional work has shown that acute predator stress impairs long-term hippocampal-dependent spatial memory and this impairment is associated with altered gene expression in the hippocampus and the prefrontal cortex (Diamond et al 1999;Sandi et al 2005;Woodson et al 2003). The ability of predator stress to facilitate recall of and responsiveness to a previously conditioned context is another novel finding of this study.…”
Section: Conditioned Locomotor Arousalsupporting
confidence: 63%
“…Such disruptive effects have been shown to occur when stress is applied 30 min before a retention session, 24 h after training animals in the water maze (de Quervain, Roozendaal, & McGaugh, 1998) and when it is applied during the 30 min before testing in a radial arm water maze under a protocol in which learning was applied on the same day just before both, stress and retention testing (Diamond, Park, Heman, & Rose, 1999;Sandi et al, 2005;Woodson, Macintosh, Fleshner, & Diamond, 2003). Glucocorticoids were implicated in the impairing effect of stress, with increasing corticosterone levels being necessary and sufficient (though interacting with noradrenergic mechanisms in the basolateral amygdala) to impair retrieval when animals were tested 24 h after training (de Quervain et al, 1998;Roozendaal, Griffith, Buranday, De Quervain, & McGaugh, 2003;Roozendaal, Hahn, Nathan, de Quervain, & McGaugh, 2004).…”
Section: Extrinsic Stress and Ncammentioning
confidence: 99%
“…Glucocorticoids were implicated in the impairing effect of stress, with increasing corticosterone levels being necessary and sufficient (though interacting with noradrenergic mechanisms in the basolateral amygdala) to impair retrieval when animals were tested 24 h after training (de Quervain et al, 1998;Roozendaal, Griffith, Buranday, De Quervain, & McGaugh, 2003;Roozendaal, Hahn, Nathan, de Quervain, & McGaugh, 2004). Glucocorticoids have also been implicated, although by themselves shown not to be sufficient, to block retrieval when the effects of stress on retrieval were examined immediately after having trained rats in the radial arm water maze (Woodson et al, 2003).…”
Section: Extrinsic Stress and Ncammentioning
confidence: 99%
“…Repeated, or chronic, stress exposure is usually associated with deleterious effects on both memory consolidation and retrieval (Luine et al 1994;Newcomer et al 1999;Park et al 2001;Wright and Conrad 2005). Importantly, even after focusing on effects of acute stress on short-term memory, there are contradicting findings showing impairment or no effect (Kirschbaum et al 1996;Lupien et al 1997;Woodson et al 2003;Takahashi 2005).…”
mentioning
confidence: 99%